A framework for integrating reliability and systems engineering: proof‐of‐concept experiences. Issue 1 (13th September 2016) - Hosseini, Hossein Neizan; Welo, Torgeir
Abstract: Reliability plays a significant role in systems engineering. Adopting the reliability and systems engineering in the early system lifecycle may lead to better quality of the final product as well as more efficient usage of the resources use to launch the product. However, there is presently no concrete framework illustrating how reliability engineering can be integrated into the systems engineering life cycle. This article discusses the development of a new, integrated reliability and systems engineering framework. The approach has been applied in a case study in the form of a student project, including a multi‐disciplinary student team aiming to design, develop, build and validate the energy efficiency of a concept vehicle. Integrating traditional systems engineering strategies with reliability engineering best‐practices was found to significantly enhance not only the quality of the final product, but also to reduce the budget and time due to less late engineering changes and subsequent design iterations.